1996
DOI: 10.1159/000134149
|View full text |Cite
|
Sign up to set email alerts
|

Rat 5S rDNA spacer sequences and chromosomal assignment of the genes to the extreme terminal region of chromosome 19

Abstract: Fragments of the spacer region of genes for rat 5S ribosomal RNA (rDNA), which are tandemly repeated, were amplified by PCR with primers specific to the two ends of the coding region for 5S rRNA. Two amplified fragments of ∼1.6 kb were subcloned and sequenced. The spacer sequences showed a high degree of sequence identity to each other (99.2%) but substantial divergence from those of analogous mouse clones. The homologous regions in the mouse clones were interrupted by the duplication or deletion of small segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 7 publications
5
51
0
3
Order By: Relevance
“…A highly conserved chromosomal location of rDNA genes characterizes the karyotype evolution of this fish group (figure 5). The divergent locations of 5S and 45S rDNA loci seem to be the most common situation observed in most fish (Martins and Galetti 2001) and by far the most frequent distribution pattern observed in vertebrates (Suzuki et al 1996). In contrast, Fujiwara et al (2007) indicated that the 5S and 45S rDNA loci are linked on the same chromosome.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A highly conserved chromosomal location of rDNA genes characterizes the karyotype evolution of this fish group (figure 5). The divergent locations of 5S and 45S rDNA loci seem to be the most common situation observed in most fish (Martins and Galetti 2001) and by far the most frequent distribution pattern observed in vertebrates (Suzuki et al 1996). In contrast, Fujiwara et al (2007) indicated that the 5S and 45S rDNA loci are linked on the same chromosome.…”
Section: Discussionmentioning
confidence: 92%
“…The 5S rDNA is often located on a single chromosome pair in fish (Pendás et al 1994;Fujiwara et al 2007;Morescalchi et al 2008;Nirchio et al 2009) and in some mammals (Suzuki et al 1996;Laura et al 2003), probably representing a more ancient condition among animal groups. The occurrence of multiple 5S rDNA sites found in the present study, as well as in some other fish represents derived conditions in their evolutionary dynamic (Ferro et al 2001;Martins et al 2002Martins et al , 2006Zhu et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…DOI: 10.1038/sj/hdy/6800070 to map repeated units of the two rDNA families (18S-28S rDNA and 5S rDNA) and to test the presence of (GATA) n and (TTAGGG) n repeats in the genome of this species. Available literature data report on the localization of major (18S-28S rDNA) and minor (5S rDNA) ribosomal clusters on different chromosome pairs as the most frequent configuration in vertebrates (see Lucchini et al, 1993;Suzuki et al, 1996). Since very little is known about rDNAs mapping in gastropods, we employed in addition to single colour FISH, simultaneous double-colour FISH to investigate about their physical relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Eukaryote ribosomal RNA genes are organized into two different gene families: a major one encoding 18S, 5.8S and 28S rRNAs, and a small one encoding 5S rRNA. The major rDNA genes are clustered at specific chromosomal sites, which are known as nucleolar organizer regions/NORs (Suzuki et al 1996). We have shown that the asymmetrical karyotype of H. larvatus, which has three types of chromosomes (metacentric, submetacentric and telocentric chromosomes), is an important chromosome marker.…”
Section: Resultsmentioning
confidence: 99%